Dilong: Role in Peripheral Nerve Regeneration. (15th June 2011) - Chang, Yung-Ming; Chi, Wei-Yi; Lai, Tung-Yuan; Chen, Yueh-Sheng; Tsai, Fuu-Jen; Tsai, Chang-Hai; Kuo, Wei-Wen; Cheng, Yi-Chang; Lin, Chien-Chung; Huang, Chih-Yang
Abstract : Dilong, also known as earthworm, has been widely used in traditional Chinese medicine (TCM) for thousands of years. Schwann cell migration and proliferation are critical for the regeneration of injured nerves and Schwann cells provide an essentially supportive role for neuron regeneration. However, the molecular mechanisms of migration and proliferation induced by dilongs in Schwann cells remain unclear. Here, we discuss the molecular mechanisms that includes (i) migration signaling, MAPKs (mitogen-activated protein kinases), mediated PAs and MMP2/9 pathway; (ii) survival and proliferative signaling, IGF-I (insulin-like growth factor-I)-mediated PI3K/Akt pathways and (iii) cell cycle regulation. Dilong stimulate RSC96 cell proliferation and migration. It can induce phosphorylation of ERK1/2 and p38, but not JNK, and activate the downstream signaling expression of PAs (plasminogen activators) and MMPs (matrix metalloproteinases) in a time-dependent manner. In addition, Dilong stimulated ERK1/2 and p38 phosphorylation was attenuated by pretreatment with chemical inhibitors (U0126 and SB203580), and small interfering ERK1/2 and p38 RNA, resulting in migration and uPA-related signal pathway inhibition. Dilong also induces the phosphorylation of IGF-I-mediated PI3K/Akt pathway, activates protein expression of PCNA (proliferating cell nuclear antigen) and cell cycle regulatory proteins (cyclin D1, cyclin E and cyclin A) in a time-dependent manner. In addition, it accelerates G1 -phase progression with earlier S-phase entry and significant numbers of cells entered the S-phase. The siRNA-mediated knockdown of PI3K that significantly reduces PI3K protein expression levels, resulting in Bcl2 survival factor reduction, revealing a marked blockage of G1 to S transition in proliferating cells. These results reveal the unknown RSC96 cell migration and proliferation mechanism induced by dilong, which find use as a new medicine for nerve regeneration.